Pengaruh Bermain Drama Terhadap Frekwensi Menggosok Gigi Anak Usia Prasekolah Di Rumah Sakit - Eka Rokhmiati Wahyu Purnamasari; Indri Sarwilli (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Play is funnies, any spontaneous and activity provides enjoyment. Play is of vital importance forhealth development of preschool child. Play offer ample physical, emotional, cognitive and socialbenefits. The child in hospitalization expressed feelings of anger, fear, insecurity, anxiety, guilt,hopelessness and deep loneliness exacerbated. Personal hygiene is a basic human need. Insufficientbrush tooth can affect child`s health (caries). During Hospitalization, a child may be affected byless brush tooth. These Problem sholud be addressed to allow preschool child to get brush toothtwice days. Role play Dramatic Therapy is a nursing intervention, that may be applied to manageless brush tooth. This study aims to determine effect play role in frequency brush tooth in hospital.This study was conducted in preschool children who treated in hospital with 32 samples. The studywas conducted in 2 September – 27 September 2019. The study was conducted with quantitativeresearch using category comparison, pre and post test intervention. Result; there was a significantcomparison before and after play therapy and frequency brush tooth with 3 days intervention.There was p value 0.007 Role Play Dramatic Therapy in hospital can be implemented on preschoolchildren to increase healty mouth with frequency brush tooth.